On some nonlinear elliptic systems with coercive perturbations in RN - El Manouni, Said; Touzani, Abdelfattah (Revista Matemática Complutense, 2003)
A nonlinear elliptic system involving the p-Laplacian is considered in the whole RN: Existence of nontrivial solutions is obtained by applying critical point theory; also a regularity result is established.